Association of pharmacotherapy with the second hip fracture incidence in women: A retrospective analysis of the National Database of Health Insurance Claims and Specific Health Checkups of Japan. Issue 11 (27th September 2022) - Nakatoh, Shinichi; Fujimori, Kenji; Ishii, Shigeyuki; Tamaki, Junko; Okimoto, Nobukazu; Ogawa, Sumito; Iki, Masayuki
Abstract : Aim: Second hip fractures worsen the quality of life and are associated with increased mortality. We clarified the association between the pharmacotherapy and second hip fracture prevention. Methods: The relationship between the incidence of second hip fracture and the presence, type and medication possession ratio (MPR) of pharmacotherapy was investigated using medical insurance data from the National Database of Health Insurance Claims and Specific Health Checkups of Japan during April 2012 to March 2019. Results: Data of 776 040 female patients were analyzed. The 2‐year rate of second hip fractures was 3.31% ( n  = 25 684). Bisphosphonates ( n  = 148 138, 19.1%) were the most commonly used medications after primary hip fracture. Patients receiving selective estrogen receptor modulators (SERMs) had the lowest age, followed by those receiving bisphosphonates, denosumab and parathyroid hormone (PTH). The second hip fracture crude incidence was lowest in patients administered SERMs ( n  = 859, 2.44%), followed by those administered bisphosphonates ( n  = 4451, 3.00%), denosumab ( n  = 484, 3.19%), no medication ( n  = 19 017, 3.39%) and PTH ( n  = 873, 5.35%); however, the age‐adjusted incidence was the lowest in patients administered denosumab (2.22%), followed by those administered bisphosphonates (2.35%), SERMs (2.39%), no medications (3.39%) and PTH (3.67%). The MPR was highest in patients administered denosumab (60.0%). Among patients without a second hip fracture, the rate of patients with MPR ≥80% was highest among those administered SERMs (40.8%), followed by those administered bisphosphonates (38.0%), denosumab (35.4%) and PTH (12.2%). Conclusion: Differences in patient background characteristics and the rate of patients with MPR ≥80% might underlie the observed differences in the crude incidence of second hip fracture among the medication groups. Geriatr Gerontol Int 2022; 22: 930–937 . Abstract : The 2‐year rate of second hip fractures was 3.31% in Japan. Differences in patient background characteristics and the rate of patients with medication possession ratio ≥80% might underlie the observed differences in the crude incidence of second hip fracture among the medication groups.